Pengaruh Brand Trust dan Kualitas Produk terhadap Keputusan Pembelian pada Rotte Bakery Cabang Delima - Andriani, Putri; Heriyanto, Meyzi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to see how the influence of Brand Trust and Product Quality on Purchasing Decisions at Rotte Bakery Delima Pekanbaru Branch. The type of research conducted in this research is explanatory quantitative. The variables in this study are the independent variables consisting of Brand Trust and Product Quality, as well as the Dependent Variables consisting of Purchasing Decisions. The types and sources of data in this study consisted of primary data and secondary data, on the other hand a questionnaire was used to collect information from 100 respondents using an accidental sampling approach. The method used in this research is descriptive quantitative. Data analysis used includes validity test, reliability test, coefficient of determination test (), significant test with partial test (t test) and simultaneous test (f test). With the SPSS 25.0 program, data is processed for statistical analysis where the statistical test results show that the Brand Trust Variable (X1) partially has a significant effect on Purchasing Decisions (Y) then Product Quality Variable (X2) partially has a significant effect on Purchase Decisions (Y) at Rotte Bakery Branch Delima and Variables Brand Trust (X1) and Product Quality (X2) simultaneously have a significant effect on Purchase Decision (Y) at Rotte Bakery Branch Delima Pekanbaru. Keyword : Brand Trust, Product Quality, Purchasing Decisions